Search behavior, aggregate rationality and the discouraged worker effect - John K. Dagsvik; Tom Kornstad; Terje Skjerpen (Statistics Norway, Research Department, 2019)
Discouraged workers are those who have given up search due to (perceived) low chances of obtaining work. In this paper we first develop a model for the probability of being in the labor force as a function of the probability of getting an acceptable job offer. This model is based on standard search theory and it is consistent with the notion of aggregate rationality. Second, we apply this model to analyze and compare the discouraged worker effect for two categories of Norwegian females: immigrants from non-Western countries and Norwegian-born. The empirical results show that estimated search cost (disutility) per unit of time is much higher for the Norwegian-born than for immigrants whereas total (expected) estimated search cost is - on average - higher for immigrants. We also propose an alternative measure of unemployment which includes the discourage worker effect.
Keywords: C33; C35; J21; J22; J61; J64; 330; Discouraged workers; Modified unemployment rate; Aggregate rational expectations; Female immigrants; Labor force participation; Panel data; Random utility modeling